PERAN GURU PAI DALAM MENANAMKAN SOFT SKILL PADA KEGIATAN SOSIAL KEAGAMAAN DI MAN 1 WONOSOBO - Ngatek, Ahmad; Faizun, Ahmad; Linnaja, Ngatoillah (Al Jabiri: Jurnal Ilmiah Studi Islam, 2023)
This research seeks to examine: 1) the concept of the role of PAI teachers andSoft Skill socio-religious; 2) the role of PAI teachers in instillingSoft Skill socio-religious at MAN 1 Wonosobo and 3) To determine the supporting and inhibiting factors for the role of PAI teachers in instillingsoft skill on socio-religious activities. Types of qualitative field research (field research) This research uses descriptive qualitative methods. Technique collection data used, namely: observation, interviews, documentation and literature study. The research results show that: 1) The concept of the PAI teacher's role in instillingsoft skill on socio-religious activities at MAN 1 Wonosobo, namely: activities in class and activities outside of class. 2) The role of PAI teachers in instillingsoft skill socio-religious at MAN 1 Wonosobo, are: a) teachers as teachers; b) teacher as guide; and c) teachers as trainers; 3) Supporting and inhibiting factors for the role of PAI teachers in instillingsoft skill on social religious activities at MAN 1 Wonosobo. a) Supporting factors: curriculum, colleagues, andskill; and b) Inhibiting factors: environment and time.